Serum lipocalin-2 levels are positively associated with not only total body fat but also visceral fat area in Chinese men. Issue 30 (July 2016) - Luo, Yuqi; Ma, Xiaojing; Pan, Xiaoping; Xu, Yiting; Xiong, Qin; Xiao, Yunfeng; Bao, Yuqian; Jia, Weiping
Abstract : Abstract: Serum lipocalin-2 (LCN2) plays an important role in the regulation of the obesity-associated dysmetabolic state and cardiovascular disease. However, relatively little is known about the relationship between serum LCN2 levels and body fat content and distribution. We examined the associations of total body fat content and abdominal fat distribution with serum LCN2 levels in Chinese men. The study was based on a cross-sectional analysis of data for 1203 Chinese men aged 22 to 78 years from the Shanghai Obesity Study. Body fat percentage (fat%) was assessed by bioelectrical impedance analysis, and magnetic resonance imaging was adopted to quantify the visceral fat area (VFA) and subcutaneous fat area (SFA). Serum levels of LCN2 were measured with a standard enzyme-linked immunosorbent assay method. Subjects with a high fat% had higher serum LCN2 levels than those with a normal fat% regardless of their body mass index category (<25 and ≥25 kg/m 2 ). The frequency of isolated high VFA was increased with increasing quintiles of serum LCN2 levels ( P  < 0.001), but the frequency of isolated high SFA did not differ between quintiles of serum LCN2 levels. A trend of increasing VFA was observed with increasing serum LCN2 levels ( P  < 0.001). Multiple stepwise regression analysis showed that VFA was positively associated with serum LCN2 levels, independent of overall obesity and other confounding factors (standardized β = 0.082, P  = 0.008). Serum LCN2 levels are positively correlated with body fat content and independently associated with VFA in Chinese men.